Astrophysical parameters of Small Magellanic Cloud star clusters - Maia, F. (2012)
We present results obtained from CCD CT1 photometry for a sample of star clusters located in crowded fields in the Small Magellanic Cloud (SMC). The targets were studied by using spatial density maps, center finding algorithms, radial density profiles and a decontamination procedure to clean their color-magnitude diagrams (CMDs) of field stars. The results show that out of 68 objects investigated, only 37 (54 %) present a spatial stellar overdensity. Furthermore, only 8 (12 %) of them show stellar density profiles to be fitted by a King function. Ages, metallicities and color excesses of these genuine clusters were also estimated from isochrone fitting on their field decontaminated CMDs.